The physiological profile of male team handball players: What does it take to play at the elite level? - Michalsik, L. B.; Madsen, K.; Aagaard, P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Aim: To determine the physiological profile of male elite team handball (TH) players. Methods: Male elite TH field players were evaluated during tournament match-play over a six season time span using physiological measurements and by subsequent physical testing. In addition, acute fatigue development in response to simulated TH match-play was determined for maximal isometric strength (MVC) and rate of force development (RFD) with synchronous electromyography (EMG) recording, while maximal vertical jump parameters were assessed using force plate analysis. Results: Mean age and adult elite playing experience were 26.2±3.1 years (group means±SD) and 7.1±3.7 years. Wing players (84.5±5.8 kg, 184.9±5.7 cm) were less heavy and smaller (p<0.001) than backcourt players (94.7±7.1 kg, 191.9±5.4 cm) and pivots (99.4±6.2 kg, 194.8±3.6 cm). Mean heart rate and relative workload during match-play (n=41) were 163±5 beats/min and 70.9±6.0 % of VO2-max. Relative workload was lower (p<0.01) in the second half vs. the first (66.3±5.9 % vs. 75.4±5.6 % of VO2-max). Post-match blood lactate concentration and fluid loss was 4.8±1.9 mM (range: 2.8-10.8 mM) and 0.81±0.41 l pr. match. Mean VO2-max was 5.18±0.66 l O2/min corresponding to 57.0±4.1 ml O2/min/kg. Total running distance in the Yo-Yo intermittent recovery test (level 2) was 895±184 m (range: 520-1360 m), which was greater in wing players (975±123 m) than backcourt players (897±108 m) and pivots (827±264 m) (p<0.05). Fastest 30-m sprint time was 4.09±0.12 s (range: 3.87-4.28 s). The repeated sprint test (7 x 30-m) yielded a mean fatigue index of -8.1±2.7 %. Maximal "Jump and Reach" height was 0.71±0.08 m (range: 0.61-0.86 m). Maximal ball throwing speed was observed using the set shot with 3-steps run-up (92.8±5.3 km•h-1, range: 75.8-108.2 km•h-1). Decreases in quadriceps and hamstrings MVC (~10%) and RFD (~16-21%) were observed following simulated TH match-play (p<0.05, n=10). Postmatch maximal jump height (CMJ) was reduced (5.2%, p<0.01), as was also CMJ RFD (~30%, p<0.05). Conclusions: Modern male elite TH imposes moderate-to-high demands on the aerobic energy system and high demands on the anaerobic energy systems during certain periods of the match. Physical profiles differed between playing positions, with wing players covering a greater total distance in the Yo-Yo test and showing superior jumping performance and repeated sprint capacity than backcourt players and pivots. In addition, wing players were lighter, smaller, younger and less experienced on adult elite level compared to all other playing positions. Indications of temporary fatigue and a subsequent decline in performance were observed, since the relative workload decreased both in the first and in the second half of the match. Further, maximal (MVC) and rapid muscle force characteristics (RFD, impulse) were acutely affected concurrently with marked reductions in muscle EMG following simulated TH match-play, which may potentially lead to impaired functional performance.